ANALYSIS OF KI SENO NUGROHO’S DA’WAH MESSAGE IN BAGONG MBANGUN DESO CHARACTER - Nasrin, Rahmad; Najiyah, Nana (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2023)
Wayang (shadow play), is a cultural art form utilized by Wali Songo for spreading Islam in Indonesia. Currently, Ki Seno Nugroho uses Wayang to preach and promote goodness. This library research is classified as qualitative research. The outcomes of the study consist of the three primary da’wah(da’wah) messages: the message of faith, moral messages, and Islamic law messages. With a delivery method by the Qur'an, especially using Islamic wisdom (hikmah) and the principle of giving out guidance that pushes into desiring truth (the Mauidzah Al Hasanah), and arguing in a manner that is respectful and constructive, the Wayang shadow play media integrates entertainment and da’wah messaging.  Wayang shadow play not only depicts real-life scenarios but also serves as a source of guidance and amusement.